{5-endo-trig radical cyclizations: Disfavored or favored processes?} - Chatgilialoglu, C; Ferreri, C; Guerra, M; Timokhin, V; Froudakis, G; Gimisis, T. (J. Am. Chem. Soc., 2002)
Relative kinetic data were determined for the 5-endo-trig cyclization of radical 12 compared to hydrogen abstraction from (TMS)(3)SiH in the temperature range of 344-430 K, which allows for the estimation of a rate constant of 2 x 10(4) s(-1) at 298 K with an activation energy of ca. 9 kcal/mol for the cyclization process. The 5-endo-trig cyclization of a variety of radicals that afford five-membered nitrogen-containing heterocycles was addressed computationally at the UB3LYP/6-31G* level. The 5-endo vs 4-exo mode of cyclication and the effect of delocalization of the unpaired electron in the transition state were investigated. Because the ring formed during cyclization contains five sp(2) centers, electrocyclization via a pentadienyl-like resonance form was also considered. For comparison, similar calculations were performed for 4-penten-1-yl and related radicals. The factors that affect the activation energies of homolytic 5-endo-trig cyclization were determined. In the absence of steric or conformational effects, the endo cyclization to form the five-membered ring was strongly favored over exo cyclization to form the four-membered ring not only on thermodynamic grounds but also kinetically. When a substituent on the double bond was able to delocalize the unpaired electron in the transition state of the 4-exo path, the two modes of cyclization became kinetically comparable. These results have an important bearing on the generalization of the Baldwin-Beckwith rules, which classified the 5-endo-trig radical cyclization as a "disfavored" process.